2008
DOI: 10.1021/bc800233a
|View full text |Cite
|
Sign up to set email alerts
|

3-D Tissue Culture Systems for the Evaluation and Optimization of Nanoparticle-Based Drug Carriers

Abstract: Nanoparticle carriers are attractive vehicles for a variety of drug delivery applications. In order to evaluate nanoparticle formulations for biological efficacy, monolayer cell cultures are typically used as in vitro testing platforms. However, these studies sometimes poorly predict the efficacy of the drug in vivo. The poor in vitro and in vivo correlation may be attributed in part to the inability of twodimensional cultures to reproduce extracellular barriers, and may also be due to differences in cell phen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
164
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(165 citation statements)
references
References 79 publications
1
164
0
Order By: Relevance
“…To name a few, these obstacles include the drugs': low solubility, environmental or enzymatic degradation, fast clearance rates from the body, non-specific toxicity and inability to cross the biological barriers [32,33]. In order to overcome these obstacles, drug delivery carriers are being used, most of which are based on polymers [32][33][34]. Released drug concentration over time.…”
Section: Drug Deliverymentioning
confidence: 99%
“…To name a few, these obstacles include the drugs': low solubility, environmental or enzymatic degradation, fast clearance rates from the body, non-specific toxicity and inability to cross the biological barriers [32,33]. In order to overcome these obstacles, drug delivery carriers are being used, most of which are based on polymers [32][33][34]. Released drug concentration over time.…”
Section: Drug Deliverymentioning
confidence: 99%
“…Not only cellular organisation and polarisation are lost in classical 2D monocultures, cells also fail to produce an in vivo-like extracellular matrix (ECM). Cells are still able to produce and secrete ECM proteins in a 2D environment but the extent of ECM production is altered and the barrier formed is less dense and incomplete in comparison to the in vivo ECM 207 . This ECM is a very important factor as it is a natural barrier with small pores and therefore limits NP diffusion into a tissue 208 .…”
Section: The Effect Of a 3d Environmentmentioning
confidence: 99%
“…It was, for example, shown by Kuo et al that the epithelialmesenchymal-transition, which is a hallmark in the metastatic process, is promoted for several cancer cell lines when they are cultured as spheres 210 . Thus, it can be concluded that the cultivation conditions have a major influence on the cellular phenotype and function and that cellular responses following NP exposure are therefore likely to be drastically altered in a 3D model when compared to a conventional monolayer 207 .…”
Section: The Effect Of a 3d Environmentmentioning
confidence: 99%
“…Author: Please check whether the author names and journal title are okay as amended in reference 'Goodman et al (2009)…”
Section: Q1mentioning
confidence: 99%